A Novel Fault Distance Estimation Method for Voltage Source Converter-Based HVDC Transmission Lines. Issue 16 (7th May 2021) - Swetapadma, Aleena; Agarwal, Shobha; Ranjan, Ashish; Abdelaziz, Almoataz Y.
Abstract: In this work, a digital fault locator has been designed using Arduino for bipolar VSC–HVDC transmission lines based on the ratio of voltage to current signals from source end. Current and voltage signals of only rectifier end have been processed with discrete wavelet transform using DB-4 as the mother wavelet. After the signals are decomposed using wavelet up to level 4, approximate coefficients are taken. Standard deviation is then calculated and given as input to the fault locator designed in Arduino. Fault location logic has been designed in Arduino using the input features. Various fault cases are tested using proposed fault locator to check the effectiveness of the method. Percentage error in fault location estimation is within 1%. Some of the advantages of the proposed digital fault locator are no requirement of communication link, reaches setting is up to 99.8% of line length, percentage error is within 1%, and lower implementation cost. Hence the proposed digital fault locator can be implemented is a real power system effectively.